HUBUNGAN INFLASI, PERTUMBUHAN LABA DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PADA PT GARUDA INDONESIA (PERSERO) TBK PERIODE 2013-2024 - Dessy Naomy Andhiny Hutagalung; Yulian Bayu Ganar (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
Abstract.  This study aims to analyze the effect of inflation, profit growth, and company size on stock returns of PT Garuda Indonesia (Persero) Tbk during the period 2013–2024. This study uses a quantitative approach with secondary data obtained from the company's financial statements and inflation data published by the Central Bureau of Statistics. The analysis method used is multiple linear regression. Hypothesis testing is carried out through the Pearson product moment test to determine the relationship between independent variables and the dependent variable. The results of the study indicate that inflation has no relationship with stock returns of PT Garuda Indonesia (Persero) Tbk as indicated by the calculated r value of 0.132 (<r table 0.5760). Profit growth also has no relationship with stock returns as indicated by the calculated r value of 0.143 (<r table 0.5760), which indicates that changes in company profits have not been a primary consideration for investors in determining the level of stock returns. And, the size of the company measured by total assets has no relationship to stock returns with a calculated r value of -0.111 (< t table 0.5760), so that the size of the company's assets does not directly reflect the company's ability to provide returns to investors.